Development of in vitro transcribed RNA interference activators for the therapeutic inhibition of the hepatitis B virus - Shrilall, Creanne Jizell (University of the Witwatersrand, Johannesburg, 2024)
The current mainstream treatments available for patients who are chronically infected with the hepatitis B virus (HBV) are capable of suppressing viral replication, however these therapeutic strategies cannot eradicate the virus. Thus, the development of novel therapeutic strategies capable of eradicating the virus are urgently needed. The RNA interference (RNAi) pathway can be exploited by introducing RNAi activators such as primary microRNA (pri-miRNA) mimics into cells to silence genes of interest. The exploitation of the RNAi pathway by employing DNA expression cassettes that endogenously express pri-miRNA mimics which target the hepatitis B x protein (HBx) sequence has demonstrated to be efficient in inhibiting HBV replication. However, achieving safe, efficient, and cost-effective delivery remains amajor challenge. The delivery of RNA therapeutics using non-viral vectors is safer and more cost-effective than the delivery of DNA therapeutics using viral vectors, and the use of chemically synthesised small interfering RNAs (siRNA) is expensive whereas in vitro transcription offers a cheaper alternative. Therefore, the purpose of this study was to in vitro transcribe pri-miRNA mimics that target the HBx sequence which is common to each of the viral transcripts. The rationale was that simultaneously targeting the viral transcripts may reduce viral protein production, thereby removing their immunosuppressive effects, which can potentially reactivate the host’s natural defences to clear the virus. In this study, several pri-miR-31 mimics were successfully in vitro transcribed and assessed in cultured mammalian cells. The results obtained demonstrated the mimics to modestly inhibit viral replication, however these constructs were also shown to induce non-specific silencing, activate the interferon response, and were inefficiently processed into the expected guide sequences. Nevertheless, improvements can be made to the system to promote safe and efficient gene silencing. The modest inhibition demonstrated could have been attributed to inefficient processing due to the activation of the interferon response and limited trafficking of the pri-miR-31 mimics into the nucleus. The use of chemically modified nucleotides and employing precursor miRNA (pre-miRNA) may improve the safety and efficacy of these constructs. Therefore, this study demonstrated the potential of the in vitro transcribed miRNA mimics in inhibiting HBV, however improvements to the system could increase viral replication inhibition and reduce the immunogenicity of these constructs
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2024
Keywords: HBV; RNAi; Pri-miRNA; Artificial microRNA; UCTD; SDG-3: Good health and well-being